Invarianceness of higher order united scaled-invariants - Draman @ Muda, Azah Kamilah; Shamsuddin, Siti Mariyam; Darus, Maslina (2007)
This paper presents an alternative formulation of invariant moments using higher order united scaled-invariants for unequal scaling images. Moments invariants have been proposed as pattern sensitive features in classification and recognition applications. Hu was the first to introduce the concept of invariants based on combinations of regular moments using algebraic invariants. In this study, we consider unconstrained handwritten words of different presentations. Results of computer simulations for images of unequal scaling are also included verifying the validity of the method proposed.